The Role of Zaqah, Infaq, Sadaqah in Improving Economic Welfare - Rachmatika, Tisa Nadia (JEMBA: Journal of Economics, Management, Business and Accounting, 2024)
Indonesia as a country that has a Muslim majority population, has a great opportunity in the management of zakat, infaq, and sadaqah (ZIS). The occurrence of inequality related to social and economic problems causes the standard of living to be lower, thus affecting the occurrence of poverty. ZIS is used to help people who are experiencing difficulties because ZIS funds are capital for improving the economy and social welfare. The government is obliged to manage ZIS funds through the authorized institution to manage them, so the government establishes a ZIS management institution so that it can be legally accountable. The distribution procedure is carried out in 2 ways, namely by distribution and utilization.